Islamic faith in Malaysia: Current issues and challenges - Engku Ahmad Zaki, Engku Alwi; Nor Aini, Abu Bakar; Roose Nilawati, Subki (2014)
This article discusses the current challenges concerning the faith of Muslims in Malaysia. Generally, there are two major challenges: the internal challenges and external challenges. These challenges are pressing and stressing the lives of Muslims. In order for Muslims to face these challenges, they need to have a very strong determination to stay true to the teachings of al-Quran and al-Sunnah, for only these two can help safeguard the Muslims. Furthermore, both al-Quran and al-Sunnah act as major impetus towards community excellence in the various fields of life.